2020
DOI: 10.1007/s00018-020-03560-5
|View full text |Cite
|
Sign up to set email alerts
|

How much, if anything, do we know about sperm chromosomes of Robertsonian translocation carriers?

Abstract: In men with oligozoospermia, Robertsonian translocations (RobTs) are the most common type of autosomal aberrations. The most commonly occurring types are rob(13;14) and rob(14;21), and other types of RobTs are described as ‘rare’ cases. Based on molecular research, all RobTs can be broadly classified into Class 1 and Class 2. Class 1 translocations produce the same breakpoints within their RobT type, but Class 2 translocations are predicted to form during meiosis or mitosis through a variety of mechanisms, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 173 publications
(207 reference statements)
2
13
1
1
Order By: Relevance
“…The proportion of meiotic products from adjacent segregation modes in RT carriers analyzed in this study is consistent with reports for domestic species such as bulls, boars and mice (2.58–5.42%, 3.16%, and 8–11.5%, respectively) [ 64 , 65 , 66 , 67 ]. These findings may suggest a low negative effect on the reproductive fitness of heterozygous carriers of RT reported here for MAM, unlike that reported for several RT in humans where there is a wide variation in reproductive impact (0.2–49.1% of adjacent segregation products) [ 68 ].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The proportion of meiotic products from adjacent segregation modes in RT carriers analyzed in this study is consistent with reports for domestic species such as bulls, boars and mice (2.58–5.42%, 3.16%, and 8–11.5%, respectively) [ 64 , 65 , 66 , 67 ]. These findings may suggest a low negative effect on the reproductive fitness of heterozygous carriers of RT reported here for MAM, unlike that reported for several RT in humans where there is a wide variation in reproductive impact (0.2–49.1% of adjacent segregation products) [ 68 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Errors in meiosis are the result of the behavior of those chromosomes involved in the translocation and their trivalent during the first meiotic segregation. [ 40 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sperm-FISH studies revealed that different translocation types displayed different proportion of alternate segregation, ranging from 76 to 89%. Besides, the sperm aneuploidy that was not involved in a particular translocation exhibited an increased frequency, which might increase the probability of chromosomal abnormalities in embryos ( Hajlaoui et al, 2018 ; Wiland et al, 2020 ). On the contrary, Huang et al (2010) found that genders of the carriers and translocation type have no effect on the meiotic segregation of the trivalent structure.…”
Section: Discussionmentioning
confidence: 99%
“… Hajlaoui et al (2018) reported that ICE was observed by sperm FISH studies and contributed to higher rates of abnormal prenatal aneuploidy in sperm, then increasing the probability of chromosomal numerical abnormalities in embryos. Wiland et al (2020) found most infertile Robertsonian carriers exhibited an increased frequency of aneuploidy that was not involved in a particular translocation in sperm and might result in the abnormal development of embryos. In addition, Gianaroli et al (2002) obtained similar results by analyzing day 3 embryos of Robertsonian translocation carriers with FISH technology.…”
Section: Introductionmentioning
confidence: 99%
“…These processes can produce highly variable and unique breakpoints. Class 2 RTs might also occur due to telomere stress caused by the knockdown of telomere-binding protein TRF2 that coat telomeres on the p-arm and lead to chromatin decondensation, RNA polymerase I-mediated rDNA transcription, and chromothripsis, characterized by clustered genomic rearrangements of the involved chromosomes [5,7].…”
Section: Introductionmentioning
confidence: 99%